Effect of Henderson’s Need Theory–Based Nursing Care on Medication Adherence among Patients with Tuberculosis: A Quasi-Experimental Study - Wahyuni, Tri; Jiu, Cau Kim; Ariyanti, Sri (Chakra Brahmanda Lentera Institute, 2026)
Background: Medication adherence remains a major challenge in tuberculosis (TB) management, particularly in low- and middle-income countries where socioeconomic and health system barriers affect treatment continuity. Although educational and psychosocial interventions have shown benefits, the application of structured nursing theories in TB care is still limited. This study aimed to examine the effect of Henderson-based nursing care on medication adherence among TB patients Methods: This quasi-experimental study with a pretest–posttest control group design followed the TREND reporting guideline. A purposive sampling procedure was conducted by screening outpatient TB registries and applying predefined inclusion and exclusion criteria, resulting in 60 eligible participants (intervention n = 30; control n = 30). The independent variable was nursing care based on Henderson’s fourteen fundamental needs, while the dependent variable was medication adherence. Adherence was measured using a validated Medication Adherence Scale (Cronbach’s α = 0.87). Before parametric testing, assumptions of normality and homogeneity of variance were examined. Paired and independent t-tests were performed, and ANCOVA was used to control for age, education level, and treatment duration. Effect size (Cohen’s d) and 95% confidence intervals (CI) were calculated. Results: Baseline characteristics were comparable between groups (p > 0.05). In the intervention group, mean adherence scores increased from 68.7 ± 8.9 to 88.3 ± 6.4 (mean difference = 19.6; 95% CI: 16.1–23.1; p < 0.001), representing a large effect size (Cohen’s d = 2.52). The control group showed no significant improvement (mean difference = 2.4; p = 0.27). The adjusted mean difference between groups at posttest was 16.8 points (p < 0.001). Additionally, the proportion of patients classified as having high adherence increased substantially in the intervention group compared to the control group. ANCOVA confirmed a significant intervention effect (F = 64.82; p < 0.001), independent of demographic covariates. Conclusion: Henderson’s Need Theory–based nursing care significantly improves medication adherence among TB patients and demonstrates a large clinical effect. Integrating structured, theory-driven nursing interventions into routine TB services may strengthen adherence-focused care, enhance patient independence, and contribute to improved treatment completion rates in resource-limited settings.